Meningkatkan Aktivitas Belajar Siswa dengan Menggunakan Metode Peta Konsep (Concept Mapping) pada Mata Pelajaran IPA Kelas V Sekolah Dasar - Yuliza, Yuliza; Sumianto, Sumianto; Rizal, Muhammad Syahrul (Faculty Of Education, 2022)
This research is based on passive student learning activity on science subjects class v in state elementary school 012 Langgini sub-district of Bangkinang Kampar. One of solution to overcome this problem by using Concept Mapping method of (Concept Mapping). The purpose of this study to determine the increase in student learning activities using the Concept Mapping method of (Concept Mapping) on the Subjects of Science Class V Primary School. The method of this research is Class Action Research (PTK) executed in two cycles. collection techniques in the form of observation, interview, documentation. The result of this research can be concluded that student learning activity on cycle I that is, very active student as much as one people (4,45%), active students as much as 10 people (45,45%), quite active students as much as 10 people (45,45%), passive students as much as 1 people (4,45%), in this one cycle belongs to a fairly active category with an average of 50%. And in the cycles II of very active students as much as 7 people (81,82%), active students as much as 11 people (50%), quite active students as much as 4 people (18,18%), passive students as much as 0 people (0%), in cycles II this increases in the active category with the average 67,23%.